Studi Simbolisme Nama Dalam Agama Dan Identitas Budaya Pada Masyarakat Bali Dan Lombok Barat - Ida Bagus Gde Yudha Triguna; I Putu Suweka Oka Sugiharta; Dewi Rahayu Aryaningsih (Jurnal Penelitian Agama Hindu, 2026)
A name is not merely a personal label; it represents a complex symbol encompassing social identity, power relations, spiritual significance, and cultural unification. This article explores the role of names in Hindu communities in Bali and West Lombok through four key lenses: as markers of individual and social identity, as instruments for sustaining traditional hierarchies, as symbols of religious meaning and spiritual protection, and as representations of identity in the digital age. Utilizing a symbolic-cultural and interdisciplinary approach, the study demonstrates how names serve both cognitive and performative functions-shaping identity, reinforcing authority, and mediating between the seen (sekala) and unseen (niskala) dimensions of life. In the last decade, digital transformation has introduced new layers of meaning, as names increasingly operate as online identities through social media, localized scripts in domain names, and digital administrative platforms. Despite these changes, symbolic and spiritual meanings remain robust, supported by processes of cultural adaptation and innovation. The article concludes that the cultural significance of names in Bali and West Lombok reflects an ongoing negotiation between tradition and modernity, emphasizing the importance of symbolic interpretation and culturally grounded digital practices for heritage preservation.